Resepsi Tradisi Khataman Al-Qur’an di Masyarakat Sulawesi - Syarif Syarif; Saifuddin Zuhri Qudsy; Wan Khairul Aiman Wan Mokhtar (Universitas Islam Negeri Sunan Kalijaga, 2023)
The Messawe tradition in Saiyyang Pattuqduq To Tammaq Mangayi in Mandar, West Sulawesi, represents an aesthetic reception of the Qur’an that involves a khatam ceremony with local cultural influences. This research aims to understand how this tradition functions as an expression of the collective identity of the Mandar people and the relationship between the Qur’anic text and the cultural practices. The research employs a qualitative methodology, including participant observation, in-depth interviews, and literature review. The findings indicate that first, this tradition reflects an aesthetic reception of the Qur’an that focuses not only on recitation but also on cultural and spiritual symbolism; second, the Messawe procession integrates local cultural elements with religious reverence, strengthening the collective identity of the Mandar community; third, this tradition demonstrates how sacred texts are responded to creatively and aesthetically, creating a relationship between religion and culture. The contribution of this research lies in a more holistic understanding of the role of the Qur’an in the social and cultural life of Muslims in Indonesia.